2021
DOI: 10.1038/s41467-021-26431-4
|View full text |Cite
|
Sign up to set email alerts
|

Daily caloric restriction limits tumor growth more effectively than caloric cycling regardless of dietary composition

Abstract: Cancer incidence increases with age and is a leading cause of death. Caloric restriction (CR) confers benefits on health and survival and delays cancer. However, due to CR’s stringency, dietary alternatives offering the same cancer protection have become increasingly attractive. Short cycles of a plant-based diet designed to mimic fasting (FMD) are protective against tumorigenesis without the chronic restriction of calories. Yet, it is unclear whether the fasting time, level of dietary restriction, or nutrient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 81 publications
3
41
0
2
Order By: Relevance
“…Low glucose conditions are linked to increased transcription of genes that render T cells dysfunctional [42]. Nevertheless, T cells with increased glycolytic activity characterized by heightened mTOR pathway signaling can show low persistence, antigen recall response, and proliferative capacity [39][40][41]. Conversely, inhibiting mTOR signaling with rapamycin was shown to increase T cell persistence [43].…”
Section: Pre-clinical Evidence Shows That Stf Can Decrease Immunosupp...mentioning
confidence: 99%
See 1 more Smart Citation
“…Low glucose conditions are linked to increased transcription of genes that render T cells dysfunctional [42]. Nevertheless, T cells with increased glycolytic activity characterized by heightened mTOR pathway signaling can show low persistence, antigen recall response, and proliferative capacity [39][40][41]. Conversely, inhibiting mTOR signaling with rapamycin was shown to increase T cell persistence [43].…”
Section: Pre-clinical Evidence Shows That Stf Can Decrease Immunosupp...mentioning
confidence: 99%
“…In contrast, the tumor promoting myeloid derived suppressor cells (MDSCs) do not benefit from hematopoietic regeneration [40]. One study showed that the MDSC (CD11b+, Gr1+) frequency was similar in peripheral blood mononuclear cells (PBMCs) but reduced in the spleen after two cycles of 4-day FMD (with 50% or 70% calorie restriction) followed by a 10-day ad libitum diet in a 4T1 breast cancer mouse model [40]. Moreover a significant reduction of tumor-resident MDSCs and an increased T cell to MDSC ratio in PBMCs was detected [53].…”
Section: Pre-clinical Evidence Shows That Stf Can Decrease Immunosupp...mentioning
confidence: 99%
“…These molecular events ultimately impact SC “performance” and prevent SC transformation into CSCs. Accordingly, mTOR, AMPK and SIRT1 have been found deregulated in tumors [ 58 , 64 , 65 ] and in correlation with lifestyle factors lowering ATP, such as CR and exercise, which activate AMPK and are associated with lower cancer risk [ 6 ].…”
Section: Molecular and Cellular Effects Of Diet On Stem Cellsmentioning
confidence: 99%
“…Dietary patterns, foods and bioactive food compounds have been found to significantly modify lifespan and health in diverse organisms such as yeast, worms, flies, and mammals [ 5 ] and to affect cancer risk and tumor growth, directly or indirectly participating in the cancer process with a profound impact on all cancer’s hallmarks [ 5 , 6 , 7 , 8 , 9 ]. Food quality (what we eat), food quantity (how much we eat) and meal frequency (when we eat) are all aspects that weigh in on the impact of diet on our health system.…”
Section: Introductionmentioning
confidence: 99%
“…In obese patients, caloric restriction–induced weight loss is not further improved by time-restricted feeding (eating only between 8:00 am and 4:00 pm), suggesting that global caloric intake is the most important determinant of the metabolic consequence of fasting ( 3 ). However, when applied to mice, continuous caloric restriction appears to be more efficient in reducing the development and progression of cancer than intermittent fasting ( 4 ). Of note, a single fasting cycle of 48 hours administered together with immunogenic chemotherapeutics (such as anthracyclines or oxaliplatin) alone or together with PD-1 blockade improves tumor growth reduction ( 5 7 ).…”
Section: Fastingmentioning
confidence: 99%